TB vaccine development: where are we and why is it so difficult? - Wilkie, M; Mcshane, H (2014)
The development of an effective TB vaccine remains paramount to achieving the goal of global eradication of TB by 2050. The only licensed vaccine, BCG, has variable efficacy and is poorly effective in high burden countries. The development of promising candidate vaccines to either 'boost' a BCG primed immune system or replace BCG altogether is a key area for innovative research. Here, we discuss some of the issues encountered in the development of potential candidate vaccines and the future challenges.